Performance improvement of biomass combustion-basedstove byimplementing internally air-distribution. Issue 1 (March 2021) - Simanjuntak, J P; Daryanto, E; Baharuddin,; Tambunan, B H
Abstract: This research aimed to enhance the performance of biomass combustion-based stove. Thermal performances were assessed in terms of power output (Pout ), specific fuel consumption (SFC), thermal efficiency (ηth ), and burning rate (BR). These performances were expected to meet the minimum standards established by the Indonesian biomass stove alliance regarding the use of a healthy and energy-saving of biomass stove in Indonesia. The stove tested was an improved stove with an advantage on the air distributor by adding a component to administrate air combustion needed placed on the centre of the combustion zones. This is a very effective way to distribute air for combustion required where the air could reach all the fuel and the combustion product that occupy entire the combustion zones to ensure high combustion zone temperature. Coconut shell was used as feedstock. This biomass was found abundant in Indonesia and was widely used as heat source by burning it directly. The coconut shell was sized uniformly about 5 cm x 5 cm, dried by utilizing sun energy. To estimate the stove performances, several combustion tests was carried out where the air flow rate into the stove (Qa ) and the amount of biomass fuel (mb ) referred as the air–fuel ratio (A/F) were considered. The Water Boiling Test (WBT) was performed to assess this improved stove. Parameter required such as initial mass of coconut shell, the mass of residual ash, the initial mass of water, mass of water after boiling, and the time required to boil as well as combustion flame temperature were recorded and used to determine the performance of the improved stove studied.